A Critical Review on the Book The Principles of Behavioral Economics: Individual Decision-Making - Ali Saeedi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Recent years have experienced affluent literature in behavioral economics in Persian scope. The Principles of Behavioral Economics: Individual Decision-Making written by Maryam Haji-MollaDarvish is one of these works which is reviewed and criticized in this paper. The focus on the book is on individual decision-making and to this extent, after introducing neoclassic models, the theories of behavioral economics are discussed. However, most parts of the book are devoted to introducing neoclassic models while seems unnecessary. The book lacks any coherent theme or main idea and it is just a collection of discussions in behavioral economics. Having no discussion about behavioral issues of Iranian economics has unleashed the book just as a translation work. In spite of insisting on the complementary role of behavioral economics for neoclassic one and not rejecting it, most behavioral economists declare it as a heterodox school against mainstream neoclassic economics. The book is suitable as an auxiliary resource for microeconomics 1 and behavioral economic course.